Challenging glyphosate resistance EPSPS P106S and TIPS mutations with soybean competition and glyphosate: implications for management - Barroso, Arthur Arrobas Martins (2022)
BACKGROUND: Eleusine indica (L.) Gaertn. (goosegrass) is a major weed in global cropping systems. It has evolved resistance to glyphosate due to single Pro-106-Ser (P106S) or double Thr-102-Ile + Pro-106-Ser (TIPS) EPSPS target site mutations. Here, experiments were conducted to evaluate the single effect of soybean competition and its combined effect with a glyphosate field dose (1080 g ae ha−1) on the growth and fitness of plants carrying these glyphosate resistance endowing target site mutations. RESULTS: TIPS E. indica plants are highly glyphosate-resistant but the double mutation endows a substantial fitness cost. The TIPS fitness penalty increased under the effect of soybean competition resulting in a cost of 95%, 95% and 96% in terms of, respectively, vegetative growth, seed mass and seed number investment. Glyphosate treatment of these glyphosate-resistant TIPS plants showed an increase in growth relative to those without glyphosate. Conversely, for the P106S moderate glyphosate resistance mutation, glyphosate treatment alone reduced survival rate, vegetative growth, aboveground biomass (34%), seed mass (48%) and number (52%) of P106S plants relative to the glyphosate nontreated plants. However, under the combined effects of both soybean competition and the field-recommended glyphosate dose, vegetative growth, aboveground biomass, seed mass and number of P106S and TIPS plants were substantially limited (by ≤99%). CONCLUSION: The ecological environment imposed by intense competition from a soybean crop sets a significant constraint for the landscape-level increase of both the E. indica single and double glyphosate resistance mutations in the agroecosystem and highlights the key role of crop competition in limiting the population growth of weeds, whether they are herbicide-resistant or susceptible. © 2022 Society of Chemical Industry.